Influence of the quality of the opponent on physical, technical, and tactical performance of elite female soccer players in international competitions - Villaseca-Vicuña, R.; Pérez-Contreras, J.; Merino-Muñoz, P.; Morales-Acuña, F.; Giráldez, J.; Zabaloy, S. (Sport Sciences for Health, 2024)
Purpose Soccer is a complex sport that depends on several physical performance and technical-tactical factors. Therefore, we aimed to: i) analyze the differences in physical, technical, and tactical performance of one international team when competing against opponents divided by their world ranking (i.e., higher ranked [HR] and lower ranked [LR]) ii) explore the associations between physical, technical, and tactical measures obtained when playing against HR and LR teams.